2014
DOI: 10.4314/jae.v17i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Information Needs of Small Holder Farmers in Central Agricultural Zone of Nasarawa State

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 2 publications
2
15
0
Order By: Relevance
“…This implies that respondents will readily participate in any rice transformation programme that they are favourably disposed towards. This is in line with the finding of Salau et al (2013) which showed that the majority (86.0%) of the respondents were full time farmers. Also, 45.0% of the respondents had no minor occupation.…”
Section: Source: Field Survey (2014)supporting
confidence: 91%
“…This implies that respondents will readily participate in any rice transformation programme that they are favourably disposed towards. This is in line with the finding of Salau et al (2013) which showed that the majority (86.0%) of the respondents were full time farmers. Also, 45.0% of the respondents had no minor occupation.…”
Section: Source: Field Survey (2014)supporting
confidence: 91%
“…The result implies that the farmers fall within the range of smallholder farmers. This supported the findings of Salau, E.S., Saingbe, N.D. and Garba, M. N. (2013) in a study of Agricultural Information needs of smallholder farmers in Central Agricultural Zones of Nasarawa State which revealed that the majority (68%) of the respondents had farm sizes ranging between 1-5ha. Size of farmland is expected to aid the adoption of new technologies by farmers because farmers that lack enough farmland cannot sacrifice their land for trials of new technology.…”
Section: Socio-economic Characteristics Of Respondentssupporting
confidence: 87%
“…This is in line with the findings of the study by Meitei and Devi (2009) who reported that information related to seed varieties, pesticides and fertilizers were most needed by farmers in rural Manipur. Similarly some author also found the similar result for information needs of the farmers which is mainly information on seeds/input availability (what input to use, how much to use, when and from where to purchase inputs) (Mittal et al, 2013),diseases and pest management (Salau et al, 2013;Shanthasheela et al, 2015), water conservation, post-harvest techniques, irrigation, manure and fertilizer management (Okwu et al, (2009), modern cultivation practices, farmers training programmes, government schemes on agriculture, storage, weather information, sources of farm credit and marketing information (Meera et al, 2004;Tologbonse et al, 2008;and Jalaja et al, 2015).…”
Section: Resultsmentioning
confidence: 60%